In Planta Study Localizes an Effector Candidate from Austropuccinia psidii Strain MF-1 to the Nucleus and Demonstrates In Vitro Cuticular Wax-Dependent Differential Expression - Carolina Alessandra de Almeida Hayashibara; Mariana da Silva Lopes; Peri A. Tobias; Isaneli Batista dos Santos; Everthon Fernandes Figueredo; Jessica Aparecida Ferrarezi; João Paulo Rodrigues Marques; Joelma Marcon; Robert F. Park; Paulo José Pereira Lima Teixeira; Maria Carolina Quecine (Journal of Fungi, 2023)
Austropuccinia psidii is a biotrophic fungus that causes myrtle rust. First described in Brazil, it has since spread to become a globally important pathogen that infects more than 480 myrtaceous species. One of the most important commercial crops affected by A. psidii is eucalypt, a widely grown forestry tree. The A. psidii–Eucalyptus spp. interaction is poorly understood, but pathogenesis is likely driven by pathogen-secreted effector molecules. Here, we identified and characterized a total of 255 virulence effector candidates using a genome assembly of A. psidii strain MF-1, which was recovered from Eucalyptus grandis in Brazil. We show that the expression of seven effector candidate genes is modulated by cell wax from leaves sourced from resistant and susceptible hosts. Two effector candidates with different subcellular localization predictions, and with specific gene expression profiles, were transiently expressed with GFP-fusions in Nicotiana benthamiana leaves. Interestingly, we observed the accumulation of an effector candidate, Ap28303, which was upregulated under cell wax from rust susceptible E. grandis and described as a peptidase inhibitor I9 domain-containing protein in the nucleus. This was in accordance with in silico analyses. Few studies have characterized nuclear effectors. Our findings open new perspectives on the study of A. psidii–Eucalyptus interactions by providing a potential entry point to understand how the pathogen manipulates its hosts in modulating physiology, structure, or function with effector proteins.